Effect on extracts of Stevia rebaudiana bertoni. in ethanol induced gastric ulcer by using wister rats - Selva Kumar Chandrasekaran, Padmanaban Bashiyam, Rajesh Pandiyan, Rajesh Kannan Velu (Recent Research in Science and Technology, 2009)
The sweet herb of Paraguay, Stevia rebaudiana Bertoni produces, in its leaves, just such an alternative with the added advantage that Stevia sweeteners are natural plant products. In addition, the sweet steviol glycosides have functional and sensory properties superior to those of many other high potency sweeteners. The PESR, EESR & AESR has investigated the anti ulcerogenic activity by using Wister rats in both sexes. Oral administration of petroleum ether, ethanol & aqueous extracts of S. rebaudiana (100 & 300 mg, p.o) produced a significant (p<0.01) and dose dependent inhibition to the acute ulcer induced by Ethanol 99% of 2.5 ml/kg/body weight at once to rats and the parameters of gastric secretion were evaluated. When compared with cimetidine (100 mg/kg, p.o) volume, pH and free acidity of gastric juice in ulcerogenic property, S. rebaudiana showed the significant activity in 300 mg/kg/body weight <p0.01. They exhibited a significant (p<0.01) inhibition of gastric lesions by decreased the free acidity and the ulcer index. The inhibitory effect of the S. rebaudiana on lesions induced by stress was compared to that of cimetidine. The volume and concentration of Gastric juice were increased after oral administration of the AESR. A significant reduction of the lesion index was observed in the acute assays. An effective significant alteration in all biochemical and histopathological parameters was investigated. From this we can conclude that the S. rebaudiana having the potential effectiveness at the dose of 300 mg/kg/body weight, <p0.01 by dose dependent manner. These results suggest that leaves of S. rebaudiana having the cytoprotective property, which support the antiulcer effect of this plant in the traditional medicine.